2018
DOI: 10.1037/amp0000286
|View full text |Cite
|
Sign up to set email alerts
|

Using attachment and relational perspectives to understand adaptation and resilience among immigrant and refugee youth.

Abstract: Migration is a critical issue for child development in the 21st century. We expand on García Coll et al.'s (1996) integrative model of minority child development by drawing from principles of attachment theory and interpersonal relationships research to offer new insights into how youth manage and respond to migration experiences. Immigrant and refugee youth should experience better outcomes to the extent that they (a) maintain strong relationships with caregivers and peers who provide a sense of closeness, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 72 publications
(100 reference statements)
3
78
0
4
Order By: Relevance
“…This finding extends the existing evidence on teacher-student relationship trajectories, which showed that ethnic minority children were underrepresented in low conflict (vs. increasing conflict) trajectories (Spilt et al, 2012), and that teachers reported lower closeness and higher conflict with ethnic minority children (Bosman et al, 2018). Overall, our findings suggest distinctive relational experiences for ethnic minority adolescents in school (Juang et al, 2018;McGrath & Bergen, 2015;Sabol & Pianta, 2012), in terms of both the form of relationship trajectories (more problematic relationship trajectories for ethnic minorities) and their frequency (a higher risk of being in problematic trajectories).…”
Section: Trajectories Of Teacher-student Relationship Qualitysupporting
confidence: 84%
“…This finding extends the existing evidence on teacher-student relationship trajectories, which showed that ethnic minority children were underrepresented in low conflict (vs. increasing conflict) trajectories (Spilt et al, 2012), and that teachers reported lower closeness and higher conflict with ethnic minority children (Bosman et al, 2018). Overall, our findings suggest distinctive relational experiences for ethnic minority adolescents in school (Juang et al, 2018;McGrath & Bergen, 2015;Sabol & Pianta, 2012), in terms of both the form of relationship trajectories (more problematic relationship trajectories for ethnic minorities) and their frequency (a higher risk of being in problematic trajectories).…”
Section: Trajectories Of Teacher-student Relationship Qualitysupporting
confidence: 84%
“…Das Wohlbefinden von Kindern und Jugendlichen in der Schule ist eine wichtige Bedingung für die schulische Anpassung und hängt mit schulischen Leistungen zusammen (Hascher und Hagenauer 2011). Lernende mit Migrationshintergrund müssen sowohl sprachlich als auch kulturell anspruchsvolle Anpassungsprozesse bewältigen und gerade für sie ist ein positiver sozialer Kontext eine bedeutsame Entwicklungsbedingung (Özdemir und Özdemir 2020;Juang et al 2018;Horenczyk und Tatar 2012;Motti-Stefanidi et al 2012;Sam et al 2006). Eine deutschlandweit durchgeführte Studie zur Jugendgesundheit (KIGGS) macht in Bezug auf Heranwachsende mit Zuwanderungshintergrund auf psychologische Anpassungsprobleme aufmerksam (Hölling et al 2007).…”
Section: Schulische Eingebundenheit Von Schülerinnen Und Schülern Mitunclassified
“…Daher stellt die Förderung von Lernenden unterschiedlicher kultureller und sozialer Herkunft im schulischen Kontext eine besondere Herausforderung dar. Gerade für Lernende mit Zuwanderungshintergrund zeigt sich die besondere Relevanz der Beziehungen zu Lehrpersonen und Peers im schulischen Kontext (Özdemir und Özdemir 2020;Göbel und Buchwald 2017;Juang et al 2018). Der vorliegende Beitrag fokussiert daher vor allem sozioemotional relevante Aspekte schulischer Interaktionen als wesentliche Faktoren schulischer Integration und betrachtet dabei die Schülerinnen und Schüler und die Lehrpersonen.…”
Section: Introductionunclassified
“…Furthermore, these camps also serve as resources for formal and informal psychological support through daily retrospection sessions and personal peer and adult consulting. Immigrant youth tend to establish a sense of connection and belonging when they maintain relationships with peers who provide a sense of closeness through various interactions within the camp setting (Juang et al, 2018). While critically important, only a few studies (e.g.…”
Section: Role Of Cultural Immersion Camp For Asian American Youth Fromentioning
confidence: 99%